PENGARUH PENERAPAN SISTEM INFORMASI MANAJEMEN TERHADAP KINERJA KARYAWAPENGGUNA SISTEM INFORMASI MAKMUR (SIMAKMUR) PT PETROKIMIA GRESIK - Ifta Taqqia; Anggraeni, Rila (Jurnal Kewirausahaan dan Inovasi, 2022)
The purpose of this research is to identify and explain the effects of Management Information System (X) on employee performance (Y). Theemployees being studied are those working at the Project Agrosolution unit of PT. Petrokimia Gresik who use SiMakmur. Using probability sampling technique, 33 people were selected as the respondents. The data of this research washarvested through observations and questionnaires and was analyzed usingclassical assumption test, simple linear regression, t test, and coefficient of determination (R2) test performed in SPSS 23 for Windows. This study finds that the application of Management Information System positively and significantlyinfluences the performance of employees who work at the Project Agrosolutionunit of PT.Petrokimia Gresik and use SiMakmur.